Costs Around the First Year of Diagnosis for 4 Common Cancers Among the Privately Insured. (13th September 2022) - Shih, Ya-Chen Tina; Xu, Ying; Bradley, Cathy; Giordano, Sharon H; Yao, James; Yabroff, K Robin
Abstract: Background: We estimated trends in total and out-of-pocket (OOP) costs around the first year of diagnosis for privately insured nonelderly adult cancer patients. Methods: We constructed incident cohorts of breast, colorectal, lung, and prostate cancer patients diagnosed between 2009 and 2016 using claims data from the Health Care Cost Institute. We identified cancer-related surgery, intravenous (IV) systemic therapy, and radiation and calculated associated total and OOP costs (in 2020 US dollars). We assessed trends in health-care utilization and cost by cancer site with logistic regressions and generalized linear models, respectively. Results: The cohorts included 105 255 breast, 23 571 colorectal, 11 321 lung, and 59 197 prostate cancer patients. For patients diagnosed between 2009 and 2016, total mean costs per patient increased from $109 544 to $140 732 for breast (29%), $151 751 to $168 730 for lung (11%) or $53 300 to $55 497 for prostate (4%) cancer were statistically significant. Increase for colorectal cancer (1%, $136 652 to $137 663) was not statistically significant ( P  = .09). OOP costs increased to more than 15% for all cancers, including colorectal, to more than $6000 by 2016. Use of IV systemic therapy and radiation statistically significantly increased, except for lung cancer. Cancer surgeries statistically significantly increased for breast and colorectal cancer but decreased for prostate cancer ( P  < .001). Total costs increased statistically significantly for nearly all treatment modalities, except for IV systemic therapy in colorectal and radiation in prostate cancer. Conclusions: Rising costs of cancer treatments, compounded with greater cost sharing, increased OOP costs for privately insured, nonelderly cancer patients. Policy initiatives to mitigate financial hardship should consider cost containment as well as insurance reform.